Acute Effects of Static Stretching on Muscle Strength and Power: An Attempt to Clarify Previous Caveats - Chaabene, Helmi; Behm, David G.; Negra, Yassine; Granacher, Urs (Frontiers in Physiology, 2019)
The effects of static-stretching (StS) on subsequent strength and power activities has been one of the most debated topics in sport science over the past decades. The aim of this review is i) to summarize previous and current findings on the acute effects of StS on muscle strength and power performances ii) to update readers’ knowledge related to previous caveats and iii) to discuss the underlying physiological mechanisms of short-duration StS when performed as single-mode treatment or when integrated into a full warm-up routine. Over the last two decades, StS has been considered harmful to subsequent strength and power performances. Accordingly, it has been recommended not to apply StS before strength and power-related activities. Recent evidence suggests that when performed as a single-mode treatment or when integrated within a full warm-up routine including aerobic activity, dynamic-stretching, and sport-specific-activities, short-duration StS (≤60s per-muscle group) trivially impairs subsequent strength and power activities (∆1-2%). Yet, longer-durations StS (>60s per-muscle group) appear to induce substantial and practically relevant declines in strength and power performances (∆4.0-7.5%). Moreover, recent evidence suggests that when included in a full warm-up routine, short-duration StS may even contribute to lower the risk of sustaining musculotendinous injuries especially with high-intensity activities (e.g., sprint running and change of direction speed). It seems that during short-duration StS, neuromuscular activation and musculotendinous stiffness appear not to be affected compared with long-duration StS. Amongst other factors, this could be due to an elevated muscle temperature induced by a dynamic warm-up program. More specifically, elevated muscle temperature leads to increased muscle fiber conduction-velocity and improved binding of contractile proteins (actin, myosin). Therefore, our previous understanding of harmful StS effects on subsequent strength and power activities have to be updated. In fact, short-duration StS should be included as an important warm-up component before the uptake of recreational sports activities due to its potential positive effect on flexibility and musculotendinous injury prevention. However, in high-performance athletes, short-duration StS has to be applied with caution due to its negligible but still prevalent negative effects on subsequent strength and power performances, which could have an impact on performance during competition.